Application of the SDLC Method and Laravel Framework in Developing a Web Draft Based Company Profile Information System - Surahmat, Asep; Darmawan, Rizqi (Scientific Journal of Information System, 2024)
The development of a web-based company profile information system has become a fundamental need for organizations to increase reachability and direct customer involvement in it. In this context, structured software development methods and efficient frameworks become essential in ensuring project success. This article discusses the application of the Software Development Method (SDLC) and the Laravel Framework in developing a web-based company profile information system. The case study was conducted at CV Radar Teknologi Computer, a technology company engaged in providing software solutions. The SDLC method is used as a systematic approach to managing the entire information system development life cycle, from requirements analysis to testing and implementation. The Laravel framework was chosen to facilitate the development process by providing a strong structure and a variety of built-in features. The implementation results show the effectiveness of using SDLC and Laravel in achieving project goals in a timely manner and according to the desired specifications.